Pengaruh Penggunaan Media Visual dan Minat Belajar Siswa terhadap Hasil Belajar Matematika - Lasia Agustina (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2011)
This study aims to get empirical data and analyze the influence of the use of visual media and interest in learning of mathematics against learning outcomes. Research variables consist of: the independent variable is the visual media through a method that uses a visual method of teaching with no visual media and interest in learning, the dependent variable is learning result on math. The research was conducted on the class X SMK PGRI 20 Cibubur. The research method used was experimental research design. The research sample consists of 68 students, divided into experimental class of 34 students and a control class of 34 students. Based on hypothesis testing, the conclusion are: (1) There are differences in learning outcomes of students who are taught with the visual media is higher than students who are taught without visual media (2) There are no differences in learning outcomes of students who have high interest to students of low interest (3) there is interaction between the use of visual media with the interest of the students towards the learning of mathematics (4) In the group of students who are taught using visual media, there is no difference between students who have an interest high and students who have low interest (5) In the group of students who taught without using visual media, there is no difference between students who have high interest and low interest students who have, (6) In the group of students who have high interest, there is a difference between students who are taught using visual media and students who are taught without the use of visual media (7) In the group of students who have low interest, there is a difference between students who are taught using visual media and students who are taught without the use of visual media.